Computational Design and Parametric Optimization Approach with Genetic Algorithms of an Innovative Concrete Shading Device System. (2017) - Zani, Andrea; Andaloro, Michele; Deblasio, Luca; Ruttico, Pierpaolo; Mainini, Andrea G.
Abstract: Office buildings in contemporary architecture usually have a high value of window to wall ratio (WWR) determining transparent façade as the most important part of the building façade to control solar gains, thermal losses and visual comfort. Therefore, in order to fulfill strict National energy regulations and LEED requirements, façades require a proper balance between transparent and opaque or shaded surfaces to avoid overheating, optimizing daylighting aspects and outdoor perception. Concrete is usually used in building sector for primary structure or secondary structure of cladding solutions. With new concrete materials and innovative digital fabrication process is possible to rediscover concrete for high performance façade/shading solutions. The aim of this paper is the development of high performance concrete static shading system using computational design approach and its optimization, by genetic algorithms, based on several parameters such as radiation control, outdoor view and daylight indexes and energy performance. After the development of a geometry definition managed with a parametric modelling approach (Rhinoceros and Grasshopper), genetic algorithm optimization were used in order to define the openness's sizes and their cutting angle to minimize solar radiation entrance during year, maintaining outdoor view. The possible geometric alternatives were part of a sensitivity analysis with Radiance and Energy-plus engine to assess the shading system performance in terms of daylighting and energy use. In order to evaluate their performances a study case, a single office unit placed in Milan (Italy) was defined, considered with wall facing outdoors, having a WWR of 86%, and five surfaces adiabatic. The results shows that using this approach is possible to develop an effectiveness shading solution able to control radiation over the year and likewise guarantee a high performance regarding the outdoor perception and visual comfort.